Phytoremediation activity on heliconia psittacorum via water quality testing and bacteria identification / Siti Nurfazlina Mohd Roslan - Mohd Roslan, Siti Nurfazlina (2020)
The accumulation of contaminants capable to give negative impact towards environment in various ways. Thus, phytoremediation come as a cost-effective technology that used plant and associated microbes to outweigh the problem in soil and water contamination. Heliconia psittacorum becomes one of the plants that have potential characteristic as phytoremediation and ecological friendly. This study was aimed to analyze the concentration and identification of bacteria that could assisted in phytoremediation. Besides, the water quality was tested to correlate with the phytoremediation activity of Heliconia psittacorum. Two samples of soil and roots were prepared and serially diluted for bacteria counting. The concentration of bacteria in roots sample was 4.4 x cfu/ml, while, for soil sample was 1.5 x cfu/ml. Roots often associated with bacteria and eventually contribute to a higher concentration of bacteria compared to soils. Several suspected colonies then picked, cultured and identified based on biochemical tests and API identification kits. Seven strains of bacteria were identified consisted of Pseudomonas luteola, Serratia liquefaciens, Serratia marcescens, Enterobacter cloacae, Staphylococcus xylosus, Staphylococcus saphrophyticus and Enterococcus faecium. All bacteria that were identified provide a related background mechanism that capable to remove, transfer, stabilize contaminants and indirectly enhanced the plant growth. Besides, the water quality showed reduction in individual concentration of copper, zinc and phosphate from 0.64 mg/l to 0 mg/l, 0.173 mg/l to 0.068 mg/l, and 0.513 mg/l to 0.293 mg/l respectively. In conclusion, the concentration and identification of bacteria in root sand soil provided information regarding on the ability of these bacteria to reduce the contaminants and the water quality assessment proved the potential of Heliconia psittacorum in phytoremediation.